2021
DOI: 10.3390/microorganisms9112315
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Temporal Effects of a Mud Volcanic Eruption on the Bacterial Community and Their Predicted Metabolic Functions in the Mud Volcanic Sites of Niaosong, Southern Taiwan

Abstract: The microbial communities inhabiting mud volcanoes have received more attention due to their noteworthy impact on the global methane cycle. However, the impact of temporal effects of volcanic eruptions on the microbial community’s diversity and functions remain poorly characterized. This study aimed to underpin the temporal variations in the bacterial community’s diversity and PICRUSt-predicted functional profile changes of mud volcanic sites located in southern Taiwan using 16S rRNA gene sequencing. The physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…It has also been suggested that in some TMVs, Acholeplasmataceae spp. may represent a component of dead insects or nematodes' microbiomes [13]. Their predicted role in the community is likely in the fermentation of products from the degradation of organic matter to produce small molecules such as acetate or ethanol, which in turn may be utilized by other members of the TMV microbial community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that in some TMVs, Acholeplasmataceae spp. may represent a component of dead insects or nematodes' microbiomes [13]. Their predicted role in the community is likely in the fermentation of products from the degradation of organic matter to produce small molecules such as acetate or ethanol, which in turn may be utilized by other members of the TMV microbial community.…”
Section: Discussionmentioning
confidence: 99%
“…The information on anaerobic organoheterotrophic fermentative microorganisms, isolated from TMVs, is limited to a few reports [11,12]. Representatives of the class Mollicutes have been detected by molecular methods based on a microbial community analysis in several TMVs [13,14]; however, to date, no cultivated Mollicutes from mud volcanoes are known. The Taman Peninsula is among the regions with the most pronounced mud volcanism; the Kerch-Taman mud volcano province includes over 100 active TMVs [15].…”
Section: Introductionmentioning
confidence: 99%
“…The hypervariable V3-V4 region of the 16S rRNA gene was amplified using the following set of forward and reverse primers: Pro341F (5′–CCTACGGGNBGCASCAG–3′) and Pro805R (5′-GACTACNVGGGTATCTAATCC-3′) [ 21 ]. The PCR was carried out in a thermocycler (Px2 Thermal Cycler, Thermo, Waltham, MA, USA) with a total volume of 25 μL that contained 3 μL of the template DNA, 2X KAPA HiFi HotStart Ready Mix (12.5 μL), 400 nM of each primer, and ddH 2 O (7.5 μL).…”
Section: Methodsmentioning
confidence: 99%
“…The genus Marivirga was first established by Nedashkovskaya et al and is the sole genus of the family Marivirgaceae in the phylum Bacteroidota [1–3]. The members of the genus Marivirga are among the marine bacteria which commonly live in wet habitats [4]. At present, the genus Marivirga encompasses only five species with validly published names, Marivirga atlantica , Marivirga harenae , Marivirga lumbricoides , Marivirga sericea and Marivirga tractuosa [5–8].…”
Section: Introductionmentioning
confidence: 99%